2023
DOI: 10.1002/jbmr.4925
|View full text |Cite
|
Sign up to set email alerts
|

Acetyltransferases CBP/p300 Control Transcriptional Switch of β-Catenin and Stat1 Promoting Osteoblast Differentiation

Linlin Zhang,
Kecheng Zhu,
Jingzun Xu
et al.

Abstract: CBP (CREBBP) and p300 (EP300) are multifunctional histone acetyltransferases (HATs) with extensive homology. Germline mutations of CBP or p300 cause skeletal abnormalities in humans and mice. However, the precise roles of CBP/p300 in bone homeostasis remain elusive. Here, we report that conditional knockout of CBP or p300 in osteoblasts results in reduced bone mass and strength due to suppressed bone formation. The HAT activity is further confirmed to be responsible for CBP/p300‐mediated osteogenesis using A‐4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Additionally, Signal Transducer and Activator of Transcription 1 (STAT1) is a member of the STAT protein family and can activate signaling pathways involved in various physiological and pathological responses [ 50 ]. Multiple studies have indicated that STAT1 can induce cellular apoptosis and hinder fracture repair [ 51 , 52 ]. In conclusion, the degradable zinc scaffold/BF Exo composite implants developed in this study enhance the osteogenic, anti-osteoclastic, and pro-angiogenic capabilities during bone defect repair, which may be associated with the regulation of p38/STAT1 by BF Exo.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Signal Transducer and Activator of Transcription 1 (STAT1) is a member of the STAT protein family and can activate signaling pathways involved in various physiological and pathological responses [ 50 ]. Multiple studies have indicated that STAT1 can induce cellular apoptosis and hinder fracture repair [ 51 , 52 ]. In conclusion, the degradable zinc scaffold/BF Exo composite implants developed in this study enhance the osteogenic, anti-osteoclastic, and pro-angiogenic capabilities during bone defect repair, which may be associated with the regulation of p38/STAT1 by BF Exo.…”
Section: Discussionmentioning
confidence: 99%
“…5b ; Table 3 ) 412 . One study reported that conditional knockout of CBP or p300 in osteoblasts inhibited bone formation, resulting in reduced bone mass and strength 412 . Mechanistically, CBP/p300 HAT regulates the expression of osteogenic genes partly by activating β-catenin transcriptionally and suppressing Stat1.…”
Section: Epigenetic Modification Of Transcriptional Gene Regulationmentioning
confidence: 99%
“… 411 CBP/P300 Mediates H3K27 acetylation and the activation of Foxo1. 412 Histone deacetylases SIRT1 Enhances Runx2 trans-activation activity. 301 HDAC1 Negatively regulates osteoblast generation by reducing Osx and OCN gene promoters’ H3 and H4 acetyl labeling.…”
Section: Epigenetic Modification Of Transcriptional Gene Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoporosis signs are present in mice upon p300 inhibitor treatment. These two HATs acetylate lysine 27 of histone 3, enhancing β-catenin signaling to promote osteoblastic activity [84]. This HAT interacts with nuclear receptor corepressor and histone deacetylase 3, promoting acetyl histone enrichment at toll-like receptor 4/6 promoters for osteoclast differentiation of macrophages [85].…”
Section: Acetyl-coa As a Co-factor For Histone Acetyltransferasesmentioning
confidence: 99%